(untitled) (Ustozlar uchun, 2025)
The topic “Smart Classrooms: How AI is Transforming Traditional School Education” analyzes the role and importance of artificial intelligence in the modern education system. Smart classrooms provide a more interactive, flexible and student-centered approach to traditional education. AI technologies significantly improve the quality of education by identifying the individual needs of students, automatically assessing their knowledge level, personalizing the learning process and offering teachers intelligent tools. Smart boards, voice-controlled teaching systems, chatbots and virtual assistants are widely used in such classrooms. Artificial intelligence conducts real-time analysis, monitors student activity and provides them with customized educational materials. As a result, students acquire independent learning skills, and teachers have the opportunity to organize the lesson process more effectively. This work aims to highlight the role, advantages and future opportunities of AI technologies in the modernization of traditional school education.